Spatial distribution of air kerma rate and impact of accelerating voltage on the quality of an ultra soft X-ray beam generated by a cold cathode tube in air. (September 2015) - Ounoughi, N.; Mavon, C.; Belafrites, A.; Fromm, M.
Abstract: Ultrasoft X-ray characteristic aluminum K alpha line (Al Kα with energy of 1.5 keV) is used in radiobiological experiments to study the effect of radiation on biological matter. A simple method to generate a continuous beam of those X-ray radiations is to bombarding an aluminum target with accelerated electrons using high voltage (HV). In this work, by varying the HV we study the characteristics of a photon beam generated by means of a cold cathode transmission X-ray tube. The anode is a thin (16 μm) aluminum foil supported by a copper grid. The spatial distribution of air kerma is measured using gafchromic films of HD-810 calibrated with a parallel plate free-air ionization chamber. We show that HV strongly modifies the energetic spectrum and air kerma rate as well as its uniformity and intensity in air. Highlights: We measured energy spectrum of X-ray beam. We calibrate the Gafchromic films to measure air kerma of X-ray beam. Spatial air kerma rate is determined and interpreted. We define dimensions and position of future biological sample irradiation using Al Kα X-ray.